GURU PENGGERAK - Roslaeni (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2024)
Motivating Teacher Education is Leadership program for to become learning leaders. This program includes online training, workshops, conferences, and 6 months mentoring for aspiring teacher movers. During the program, the mover teacher continues to carry out his teaching duties as a teacher. The goals of independent learning with Motivating Teacher Education are expected to: 1) have a